The Analisis Sistem Penerapan Sikap Tawadhu di Pondok Pesantren Al-Barokah (Studi Analisis Mahasiswa Universitas Pendidikan Indonesia) - Adis Mulyadi; Maisa Siti Nabilah Mardiah; Muhammad Fauzan Kamil; tiara atikah (Jurnal Pendidikan Islam, 2023)
This research aims to: 1). Able to know the meaning of humble attitude; 2). Able to know the proper application system in a humble attitude of tawadhu and 3). Able to know the role of humility in life, especially for students at the Al-Barokah Islamic Boarding School and society in general. The research method used is descriptive qualitative with observational research methods through interviews about descriptive research, the primary data source comes from students or students at the Al-Barokah Islamic boarding school. And this study uses several methods in obtaining data, namely by direct observation and unstructured interviews, and documentation. As well as data analysis techniques using interactive models of Miles, Huberman, and Saldana which include data condensation, data presentation and drawing conclusions. Then the results of this study show: Tawadhu has a very good meaning, which is a feeling that you never feel more than anyone because you know that the Creator is omnipotent. The Role model is one of the right systems in the application of humility. And the role of tawadhu is very important, especially for students at the Al-Barokah Islamic Boarding School and generally the community in developing good character value education and being able to exert positive influence and impact on their lives.